2014
DOI: 10.1002/ccd.25532
|View full text |Cite
|
Sign up to set email alerts
|

Aspiration thrombectomy in patients undergoing primary angioplasty: Totality of data to 2013

Abstract: Our meta-analysis including all randomized controlled trials on aspiration thrombectomy to date demonstrates a significant reduction in adverse clinical outcomes including stent thrombosis compared with conventional PCI alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…Kumbhani et al 26 showed a significant reduction of reinfarction and stent thrombosis during a weighted mean duration of followup of 2.7 months. Our results at 10.4 months showed no difference in the 2 endpoints between groups; however, after stratifying the extracted outcomes according to short-(30 days) or long-term…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Kumbhani et al 26 showed a significant reduction of reinfarction and stent thrombosis during a weighted mean duration of followup of 2.7 months. Our results at 10.4 months showed no difference in the 2 endpoints between groups; however, after stratifying the extracted outcomes according to short-(30 days) or long-term…”
Section: Discussionmentioning
confidence: 97%
“…11,13,15,16,26 It has recently been suggested that even though a benefit was not observed at short-term follow-up, late mortality may be reduced by AT. 26 This prompted the question of whether the equipoise in early mortality was related to a lack of statistical precision or whether there was an actual mechanistic explanation for a potential reduction in late mortality. In a stratified analysis we found no formal interactions for the time point of evaluation of Figure 1.…”
Section: Discussionmentioning
confidence: 98%
“…Prior randomized trials and meta-analyses had shown disparate results for the short-term benefits of aspiration thrombectomy [3][4][5][17][18][19][20][21] ; however, none of the studies was designed to address the potential synergistic effect of glycoprotein IIb/IIIa inhibitors on outcomes. In the INFUSE-AMI trial, patients were randomized in a 2×2 factorial design to intralesional abciximab at the site of the infarct lesion using a special infusion catheter versus no intracoronary abciximab.…”
Section: Discussionmentioning
confidence: 99%
“…3,[17][18][19][20][21] We communicated with select authors when further article clarification was necessary.…”
Section: Data Sourcesmentioning
confidence: 99%
“…9 Subsequently, the recent large Thrombus Aspiration in ST-Elevation Myocardial Infarction in Scandinavia (TASTE) trial showed no reduction in mortality at 30 days or 1 year with routine thrombectomy. 10,11 Although an updated metaanalysis of thrombectomy that included the TASTE trial continued to suggest that a modest but clinically important benefit is possible, 12 the efficacy of this procedure remains uncertain.…”
mentioning
confidence: 99%